Enterprise Architecture Planning Sistem Informasi Akademik Dengan TOGAF ADM - Basir, Azhar; Fadlil, Abdul; Riadi, Imam (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2019)
The role of information technology greatly influences the improvement of a higher education governance, so that universities today should have models and standards that can be implemented as a reference in enhancing harmony between business strategies and information technology. Enterprise Architecture planning (EAP) is one of the methodologies that can be applied in planning information architecture, the stages in EAP consist of data architecture, application architecture, technology architecture and how the design that has been made can be implemented to support business activities, to achieve the organization's mission.